Penguatan Kesadaran Hukum Jamaah melalui Majelis Taklim: Peran Akademisi Hukum dalam Pengabdian di Masjid Sunan Giri Waru Sidoarjo - Atmari; Miftakhul Jannah; Fadhilah Rahmawati; Conita Ayu Zaqiyah; Adi Haryoto (ALKHIDMAH: Jurnal Pengabdian dan Kemitraan Masyarakat, 2023)
Low levels of legal awareness remain a challenge in fostering orderly and just social life, including among participants of Islamic study groups (majelis taklim). This community service program aims to strengthen the legal awareness of congregants through majelis taklim by involving legal academics in delivering community-based legal education at Masjid Sunan Giri Waru Sidoarjo.The method applied is a qualitative descriptive approach with a participatory strategy, implemented through legal counseling, interactive discussions, and case studies relevant to the participants’ everyday social experiences. The activities were conducted in a dialogical manner to enable participants to understand legal concepts in a more contextual and applicable way.The results show an improvement in participants’ understanding of basic legal awareness, particularly in relation to family and social issues. Participants also demonstrated a shift toward a more critical and preventive attitude regarding legal problems in their surrounding environment. In addition, active participation during discussions indicates that majelis taklim serves as an effective community-based platform for legal education. This program concludes that collaboration between legal academics and majelis taklim can serve as an effective model for strengthening community legal awareness through a humanistic, contextual, and religious-value-based approach.